Encounter, Engagement, and Exchange How Native Populations of the Americas Transformed the World - Wright, John B. (Seminar on the Acquisition of Latin American Library Materials, 2011)
Selected papers from the annual conference of the Seminar on the Acquisition of Latin American Library Materials